Impossibles encyclopédies - Timour Muhidine (Itinéraires)
R. E. Koçu was without doubt one of the most distinguished scholars on Istanbul. He seeked to describe with the rarest details the strange habits regarding the social life of Old Istanbul within the context of Ottoman and Early Republican History. His never-completed Encyclopedia remains one of the most enduring myths of contemporary Turkish Literature where major encyclopedist themes appear.